2009
DOI: 10.1097/brs.0b013e31818b8882
|View full text |Cite
|
Sign up to set email alerts
|

How Often Is Low Back Pain Not Coming From the Back?

Abstract: For patients presenting to a spine surgeon's clinic for LBP, up to 25% of patients may have significant pain contribution from the hip or SI joints, and an additional 10% will still have an undefined pain source even after diagnostic workup. This underscores the need for clinicians to be aware of nonspinal pain generators and to appropriately pursue alternative diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
226
0
19

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(245 citation statements)
references
References 41 publications
0
226
0
19
Order By: Relevance
“…19, 89, 249, 266, 318 It has been suggested that altered movements of the hip and spine may contribute to the development of low back pain, as it may alter the loads placed on the lumbar facets and posterior spinal ligaments. 1, 190 Several authors have described restricted hip mobility in patients with low back pain as an indicator of positive response to interventions targeting the hip.…”
Section: Clinical Guidelines: Interventionsmentioning
confidence: 99%
“…19, 89, 249, 266, 318 It has been suggested that altered movements of the hip and spine may contribute to the development of low back pain, as it may alter the loads placed on the lumbar facets and posterior spinal ligaments. 1, 190 Several authors have described restricted hip mobility in patients with low back pain as an indicator of positive response to interventions targeting the hip.…”
Section: Clinical Guidelines: Interventionsmentioning
confidence: 99%
“…Since treatment of disc pathology does not always result in LBP relief, interest has resurfaced in the SIJ as potential source of LBP. Recently several reports estimate that 15-30 % of LBP is caused by the SIJ [5,6]. The SIJ The members of iMIA Study Investigators/study coordinators are listed in ''Appendix' '. may be an even more common pain source after lumbar fusion [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Some patients may have lumbar fusion for misdiagnosed SIJ syndrome or some may have only lumbar fusion for lumbar pathology and SIJ syndrome. Sembrano and Polly [36] reported that up to 14.5 % of patients presenting to a spine surgeon's clinic for low back pain had SIJ pathology. In another study, Weksler et al [37] found that patients with low back pain and disc herniation who responded positively to pain provocation tests for SIJ dysfunction exhibited significant improvement in visual analogue scale (VAS) pain scores after SIJ injection.…”
Section: Pathophysiologymentioning
confidence: 99%